Transvaginal Ovarian Cyst Drainage in Third Trimester to Facilitate Vaginal Delivery - Vivienne T. Meljen; Carmen M. Avram; Nicole P. Kerner; Eleanor H. J. Rhee; Jeffrey A. Kuller; Sarahn M. Wheeler (American Journal of Perinatology Reports, 2023)
Adnexal masses in the third trimester of pregnancy may obstruct the pelvic outlet precluding labor induction and vaginal delivery. Expectant versus surgical management of adnexal cysts in pregnancy must carefully weigh maternal–fetal benefits and risks. Simple benign appearing cysts with low likelihood of malignancy may be amenable to percutaneous drainage as a bridge to interval postpartum laparoscopic cystectomy. We demonstrated posterior culdocentesis as a safe, minimally invasive technique to decompress a simple benign appearing left adnexal cyst obstructing the pelvic outlet in the third trimester at the time of labor induction to facilitate vaginal delivery and prevent primary cesarean delivery. Detailed sonographic cyst evaluation and counseling on underlying risk of malignancy must be considered to guide shared decision-making.